Pengaruh Financial Technology terhadap Indeks Pembangunan Manusia di Indonesia - Jevan Andreas Talahaturusun; Cliff Kohardinata; Luky Patricia Widianingsih (Journal on Education, 2023)
This research aims to determine the effect of financial technology (FinTech) in the form of P2P loans on the human development index with the use of credit as a control variable. These two usage variables are because credit from the banking side and P2P loans from the FinTech side are expected to provide access to public funding to improve community welfare. The method used in this research is quantitative using a multiple linear regression approach. The data used is documentation of fintech lending statistical reports and banking statistics from the Financial Services Authority and human development index data from the Central Statistics Agency. The population in this study was all provinces in Indonesia and the sample used was 33 provinces in Indonesia from 2021-2022. The results of the research show that financial technology (P2P loans) has a significant positive effect on the human development index.